2019
DOI: 10.15252/emmm.201810061
|View full text |Cite
|
Sign up to set email alerts
|

Histological hallmarks and role of Slug/ PIP axis in pulmonary hypertension secondary to pulmonary fibrosis

Abstract: Pulmonary hypertension secondary to pulmonary fibrosis (PF‐PH) is one of the most common causes of PH, and there is no approved therapy. The molecular signature of PF‐PH and underlying mechanism of why pulmonary hypertension (PH) develops in PF patients remains understudied and poorly understood. We observed significantly increased vascular wall thickness in both fibrotic and non‐fibrotic areas of PF‐PH patient lungs compared to PF patients. The increased vascular wall thickness in PF‐PH patients is concomitan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Targeting aberrant signaling of bioactive lipids can be a therapeutic strategy for COVID-19 [41,42]. We have shown that apoA-I mimetics bind [43] and remove [44] oxidized lipids from the circulation, thus reducing the oxidative stress that contributes to endothelial dysfunction, pulmonary hypertension and lung cancer in murine models of lung disease [11,[45][46][47]. Bioactive lipids may also disrupt epithelial cell tight junctions either directly [48] or through lipid raft disruption [49,50] or TNF-α signaling [51].…”
Section: Discussionmentioning
confidence: 99%
“…Targeting aberrant signaling of bioactive lipids can be a therapeutic strategy for COVID-19 [41,42]. We have shown that apoA-I mimetics bind [43] and remove [44] oxidized lipids from the circulation, thus reducing the oxidative stress that contributes to endothelial dysfunction, pulmonary hypertension and lung cancer in murine models of lung disease [11,[45][46][47]. Bioactive lipids may also disrupt epithelial cell tight junctions either directly [48] or through lipid raft disruption [49,50] or TNF-α signaling [51].…”
Section: Discussionmentioning
confidence: 99%
“…153 In this relatively easy-to-handle animal model with many variations in terms of dosage and route of delivery, muscularization of pulmonary vessels accompanied with or without the presence of mild PH has been repeatedly described. [154][155][156][157] Since elevation of RVSP in bleomycin-challenged rodents is most often modest and occurs concomitantly with the appearance of fibrotic lesions, a 2-hit rat model by sequential exposure to bleomycin and MCT was recently developed to more adequately recapitulate group 3 PH. 156,157 As revealed by histological analyses, hydroxyproline assay, lung function testing, and right heart catheterization, the combination of these insults results in pronounced fibrosis associated with altered mechanical properties of the respiratory system and a robust PH phenotype, 156,157 making this model more appropriate to assess the impact of drugs on the development of PH in preexisting pulmonary fibrosis.…”
Section: Idiopathic Pulmonary Fibrosismentioning
confidence: 99%
“…In PAH, the biological processes of PA-SMCs and PA-ECs are abnormal, characterized by increased proliferation and Expression of the microRNA-30 family in pulmonary arterial hypertension and the role of microRNA-30d-5p in the regulation of pulmonary arterial smooth muscle cell toxicity and apoptosis reduced apoptosis (9)(10)(11). miRNAs participate in the regulation of proliferation and apoptosis in numerous diseases.…”
Section: Introductionmentioning
confidence: 99%